2019
DOI: 10.3390/biomedicines7020033
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Psychological Alterations in Haemophiliac Patients

Abstract: Haemophiliacs are hereditary coagulopathies whose basic anomaly consists of the quantitative or qualitative alteration of one or more plasma proteins in the coagulation system. The objective of this review is to analyse all risk factors, predispositions and alterations to the oral-maxillofacial district in patients with haemophilia. The broader assessment also includes the psychological aspects that could affect the treatment and maintenance of oral conditions. The study takes into consideration all the works … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…Only one study reported a relapse of the disease 2 weeks after a first surgery consisting of local excision with maxillectomy [38], while 4 studies made no reference to recurrence [32][33][34]40]. These invasive surgeries often require post-surgical rehabilitations [51,52], and in some cases are made complex by the presence of local contraindications (noble anatomical structures [53][54][55][56], or systemic contraindications (general health conditions of the patient [22][23][24]26,57]). Post-surgical and infection management are important [27,28,30].…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study reported a relapse of the disease 2 weeks after a first surgery consisting of local excision with maxillectomy [38], while 4 studies made no reference to recurrence [32][33][34]40]. These invasive surgeries often require post-surgical rehabilitations [51,52], and in some cases are made complex by the presence of local contraindications (noble anatomical structures [53][54][55][56], or systemic contraindications (general health conditions of the patient [22][23][24]26,57]). Post-surgical and infection management are important [27,28,30].…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Distant metastases of MFH commonly occur via hematogenous or lymphatic spread [1,6,20,21]. Unfortunately, it is not always possible to intervene in a timely manner in these cases, due to delays related to diagnosis or systemic conditions of the patient who need adequate protocols or therapies [22][23][24]. Many syndromic patients or those suffering from systemic diseases may also present intra and post-operative complications [23,25,26] or represent a high post-surgical infection risk [27][28][29] and therefore need adequate therapies [27,30].…”
Section: Rationalementioning
confidence: 99%
“…Medications used for fibromyalgia that may be beneficial for masticatory muscle pain according to De Rossi et al [22]. There are several syndromes and diseases which, due to their characteristics, can be similar to fibromyalgia as symptoms, and which will be excluded, even though they may be concomitant; among them, there are mainly: Sjögren syndrome, due to the low nuclear antibodies contained, multiple sclerosis, other systemic neurological syndromes, arthritis and arthrosis [37,39,[58][59][60][61][62][63]. Due to the impossibility of formulating a diagnosis based on medical evidence, and especially considering the equivocal nature of fibromyalgia, there is no universally adopted therapy whose efficacy is scientifically proven, different drugs are used [59], such as non-steroidal anti-inflammatory drugs (NSAIDs), selective serotonin reuptake inhibitors (SSRIs), cannabinoids, and muscle relaxants.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…It must be borne in mind that through the instruments of the dental practice, viruses and bacteria present in the water supply are sprayed into the environment in the form of aerosols and come into direct contact with the wounds of the patient undergoing treatment. Furthermore, some patients of the dental practice are more susceptible to this route of infection given their hygienic and dental conditions [27][28][29][30][31][32][33][34][35][36].…”
mentioning
confidence: 99%